O projeto ético-político profissional do serviço social brasileiro - Abramides, Maria Beatriz Costa (2006)
The object at this thesis is the social-political direction of the Professional Ethical-political Project of the Brazilian Social Service, as denominated since ninety-decade. The third BCSW Brazilian Congress of Social Workers is the coletive and public reference of the professional project in a breakthrough with the conservatism, defining its social-political direction as a commitment with the historical and immediately interests from the working class. The ninety-decade confers theoretical maturity on to the breakthrough professional project dedicated to the marxist legacy and the marxist tradition, it understands that the profession is inserted on the social-technical labour division in the conditions of social relationship production and reproduction under capitalism. As passed by thirty years from the times of breakthrough project as a process, the theoretical and political quarrel exited and still do in the professional discussions: fighting against military dictatorship and since 1989 against VI neoliberalism. The thesis confronts some of this polemics in the way to contribute in the present and future of our professional project on the social-political direction that we had constructed and consolidated. That implies theoretical-political autonomy and independence in the social-professional acting on the immediately conquer for work and social rights; on the historical horizon fight for human emancipation